Intraspinal Transplantation of the Adipose Tissue-Derived Regenerative Cells in Amyotrophic Lateral Sclerosis in Accordance with the Current Experts' Recommendations: Choosing Optimal Monitoring Tools - Magdalena Kuzma-Kozakiewicz; Andrzej Marchel; Anna Kaminska; Malgorzata Gawel; Jan Sznajder; Anna Figiel-Dabrowska; Arkadiusz Nowak; Edyta Maj; Natalia Ewa Krzesniak; Bartlomiej H. Noszczyk; Krystyna Domanska-Janik; Anna Sarnowska (Hindawi Limited, 2018)
Stem cells (SCs) may constitute a perspective alternative to pharmacological treatment in neurodegenerative diseases. Although the safety of SC transplantation has been widely shown, their clinical efficiency in amyotrophic lateral sclerosis (ALS) is still to be proved. It is not only due to a limited number of studies, small treatment groups, and fast but nonlinear disease progression but also due to lack of objective methods able to show subtle clinical changes. Preliminary guidelines for cell therapy have recently been proposed by a group of ALS experts. They combine clinical, neurophysiological, and functional assessment together with monitoring of the cytokine level. Here, we describe a pilot study on transplantation of autologous adipose-derived regenerative cells (ADRC) into the spinal cord of the patients with ALS and monitoring of the results in accordance with the current recommendations. To show early and/or subtle changes within the muscles of interest, a wide range of clinical and functional tests were used and compared in order to choose the most sensitive and optimal set. Additionally, an analysis of transplanted ADRC was provided to develop standards ensuring the derivation and verification of adequate quality of transplanted cells and to correlate ADRC properties with clinical outcome.